Germ Cells and Gonadal Development in a Teleost, Osteochilus vittatus (Valenciennes, 1842) Exposed to Potassium Dichromate - Hillary, Sharon; Hernayanti, Hernayanti; Wijayanti, Gratiana Ekaningsih (Journal Omni-Akuatika, 2022)
Potassium dichromate, K2Cr2O7, is a well-known heavy metal, commonly used as an oxidizing and tanning agent in industrial applications. Prolonged or repeated exposure of hexavalent chromium is deemed very toxic for aquatic biota, with long lasting effect. This substance induce damage to DNA and tissue structures, as well as disruption of survival and growth rate. The present research exposed Osteochilus vittatus in larval and juvenile stages, to varying concentration of K2Cr2O7. This experiment was aimed to evaluate the effect of chromium on primordial germ cells (PGCs) and subsequently, to the subject gonadal development. The evaluation was based on paraffin-embedded section, stained with Haematoxylin-Eosin. K2Cr2O7 of 2.5 and 5 ppm were applied to four crucial developmental stages; post-hatching larvae, 1-month, 2-months, and 3-months juvenile, for 30 days. There was a consistent pattern in all test subject, in which higher concentration of K2Cr2O7 resulted in lower PGCs number and delayed gonadal appearance. Our results suggested that sublethal Cr exposure to larval stage potentially decrease PGCs and thus, hinder the formation of gonad. Regulation of Cr-containing waste disposal should be issued in near future, to prevent further damage on local freshwater fish.Keywords: Chromium, Cyprinids, Juvenile, Larvae, PGC